The Effect of Just in Time Method on Inventory Control in Children's Clothing Production Companies - Sutandi, Sutandi; Juviana, Juviana (Jurnal Logistik Indonesia, 2024)
This research aims to find out how much influence the just-in-time method has on inventory control at the CV children's clothing production company. Elshaddai, North Jakarta. This research uses quantitative methods with a population of 28 respondents. The data analysis technique used in this research is statistics. Meanwhile, the data was tested using the classic assumption test which contains validity tests, reliability tests and normality tests. Determining the results was carried out using a simple linear regression test, then continued with a hypothesis test containing a partial test (t) and a coefficient of determination test. The types of data used in research are primary data and secondary data. Then the data was processed using SPSS statistical analysis. The independent variable in this research is the just in time method, and the dependent variable is inventory control. The results of the research show that there is a significant and positive influence between the just in time method variables on inventory control of 53.4% with an R2 value of 0.534, and based on the results of the t test carried out with the results of the analysis it is known that the t count of 5.453 is greater than the t table of 2.055 , then it can be concluded that H0 is rejected and H1 is accepted, which means that the just in time method variable (X) is significant to the inventory control variable (Y).